Computed Tomography Colonography as a Sensible Option for Colorectal Cancer Screening: Evidence Based on Metanalysis - Borges, Ingrid Chaves de Souza; Cunha, Natália Costa Resende; Rassi, Amanda Marsiaj; de Oliveira, Marcela Garcia; Leão-Cordeiro, Jacqueline Andréia Bernardes; Ataides, Fábio Silvestre; Almeida, Rogério José; Vilanova-Costa, Cesar Augusto Sam Tiago; Silva, Antonio Márcio Teodoro Cordeiro (Journal of Coloproctology, 2021)
Objective This metanalysis aimed to evaluate the sensitivity and specificity of computed tomography colonography in colorectal polyp detection.Methods A literature search was performed in the PubMed and Web of Science databases.Results A total of 1,872 patients (males 57.2%, females 42.8%) aged 49 to 82 years old (mean age 59.7 ± 5.3 years) were included in this metanalysis. The estimated sensitivity of computed tomography colonography was 88.4% (46.3–95.7%, coefficient of variation [CV] = 28.5%) and the estimated specificity was 73.6% (47.4–100.0%, CV = 37.5%). For lesions up to 9 mm, the sensitivity was 82.5% (62.0–99.9%, CV = 25.1%) and the specificity was 79.2% (32.0–98.0%, CV = 22.9%). For lesions > 9 mm, the sensitivity was 90.2% (64.0–100.0%, CV = 7.4%) and the specificity was 94.7% (80.0–100.0%, CV = 6.2%). No statistically significant differences in sensitivity according to the size of the lesion were found (p = 0.0958); however, the specificity was higher for lesions > 9 mm (p < 0.0001).Conclusions Most of the studies analyzed in the present work were conducted before 2010, which is about a decade after computed tomography colonography started being indicated as a screening method by European and American guidelines. Therefore, more studies aimed at analyzing the technique after further technological advancements are necessary, which could lead to the development of more modern devices.
Keywords: virtual colonoscopy; CT colonography; optic colonoscopy; colon cancer; diagnosis